289Pharmacologic rejuvenation of senescent human cardiac stem cells enhances myocardial repair. (15th July 2014) - Avolio, E; Gianfranceschi, G; Caragnano, A; Athanasakis, E; Katare, R; Meloni, M; Beltrami, CA; Cesselli, D; Madeddu, P; Beltrami, AP
Abstract: Purpose: Cellular senescence associated with ageing and disease hampers the functional properties of human c-Kit+ Cardiac Stem Cells (CSC) in vitro. Aim of the study was to identify molecular mechanisms associated with CSC senescence and to pharmacologically modulate this latter, at the aim to improve the therapeutic potential of CSC in vivo. Methods: c-Kit+ CSC were isolated from atrial specimens of end-stage failing hearts (E-CSC, n=20) and hearts donated for transplantation (D-CSC, n=14). D- and E-CSC were compared in vitro for the expression of senescence markers and secretome. The ability of CSC's secretome to protect rat adult cardiomyocytes (CM) in vitro from a simulated ischemia-reperfusion injury was analysed. 3 molecular signalling pathways associated with cell senescence were investigated. A 3-days pharmacologic treatment with a cocktail of 10nM Rapamycin and 0.5μM Resveratrol was employed to revert E-CSC senescence in vitro. The functional recovery of SCID-Beige mice infarcted hearts injected with Vehicle (n=17), D-CSC (n=17), E-CSC (n=18) or drug-conditioned-E-CSC (n=18) (300, 000 cells/heart) was compared 14 days post-transplantation. Results: with respect to D-CSC, E-CSC show, in vitro, higher levels of senescence markers (p16, γH2AX), a blunted proliferation and a secretome strongly enriched in the pro-inflammatory IL-1β, unable to protect rat CM from apoptosis and senescence in vitro. Neutralisation of IL-1β restored E-CSC's secretome protective effect. At the molecular level, E-CSC are characterized by an hyper-activation of the canonical NFB pathway and of Caspase1, an increased activity of the TORC1 complex, an impairment of the authophagic flux and a reduction of AMPK, Akt and CREB activation. All these alterations could be successfully reverted employing a cocktail of Rapamycin and Resveratrol. The drug treatment reduced the fraction of senescent E-CSC and the amount of IL-1β secreted in vitro, thus restoring the protective effect on rat CM. Last, D-CSC but not E-CSC were able to enhance myocardial healing when injected in a mouse infarcted heart. However, the ex vivo preconditioning of E-CSC with Rapamycin and Resveratrol, prior to the in vivo transplantation, restored their reparative potential to D-CSC levels. Conclusions: we first demonstrate that senescent c-Kit+ CSC resident in human failing hearts display an impaired in vivo reparative ability; importantly, senescent CSC can be rejuvenated in vitro with a short pharmacologic conditioning, finally boosting the in vivo cardiac regeneration. These findings open new avenues to improve autologous CSC therapy in heart failure.